Ai margini dell'estetica: Alfred Schutz e l'ingenioso hidalgo (Materiali di Estetica. Terza serie, 2017)
This paper deals with Alfred Schutz’paper Don Quixote and the problem of reality which maintains that the hidalgo's story may be interpreted by James’theory of sub-universes of sense, Husserl's appresentation, and Weber's theory of types. In this perspective, Cervantes’novel represents, above all, a metaphor about the conflicts regarding the typings, the appresentations, and the durées that which very often arrive in everyday life. In this context, the variables of the social reality appear as largely intuitive so that the aesthetics and the sociology, in their traditional sense, seem to dissolve and give rise to a new synthesis.